Seed Quality Status at Farmers' Level in Hilly Tribal Region of Himachal Pradesh - K.C. DHIMAN; R.K. KAPILA; R.K. DOGRA; J.K. SHARMA (Seed Research, 2026)
Majority of the tribal farmers in the hills of Himachal Pradesh still rely on their own saved seeds for raising next season crops. A study was carried out to assess the seed quality at farmers' level of crops grown in tribal region of Himachal Pradesh by collecting seed samples at the time of sowing for 4 years consecutively. Quality analysis of seeds showed high moisture content as compared to maximum prescribed limits laid out under Indian Minimum Seed Certification Standards (IMSCS). However, most of seed samples in majority of the crops including tartary and common buckwheat, dry beans, amaranthus etc. met minimum prescribed germination laid out under IMSCS and had good field emergence. Although a similar trend was observed for minor crops of the region including wheat, barley and maize for moisture content but germination was comparatively poor in these crops apparently due to the attack of stored grain pests. Data also showed considerable variation for seed quality parameters over different years. Study indicated considerable scope for interventions at seed production, processing, particularly at storage stage to enhance the quality of seeds at farmers' level so as to minimize yield reductions due to their use by farmers.